UJI PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK BENALU TEH (Scurrula oortiana Dans.) - Reubun, Yonathan Tri Atmodjo (Parapemikir : Jurnal Ilmiah Farmasi, 2024)
The tea mistletoe plant (Scurrula oortiana Dans.) has been widely used by the community in treating diseases both modernly and traditionally. Mistletoe tea is also known to have pharmacological effects so it can be used in various diseases such as hypertension, gout, and prevention of Alzheimer's disease. The aim of this research was to determine the specific and non-specific parameter tests of mistletoe tea extract which were extracted using 96% ethanol, then carried out phytochemical screening tests, macroscopic and microscopic tests as well as testing specific and non-specific parameters. Based on the research results, it was found that the yield of mistletoe tea extract was 37.237%, specific and non-specific parameter testing showed that the drying loss value was 4,32%, the water content was 4,94%, the ethanol soluble extract content was 59,20%. Based on the test results, the ethanol extract of mistletoe tea meets the specific and non-specific parameter tests